Memórias docentes e Educação Infantil: diálogos com a formação de professores na cidade de Sorocaba - SP - Sewaybricker, Gabriela Maldonado (2021)
This research focuses on registering and understanding aspects of teacher’s education’s history for Childhood Education in the city of Sorocaba, São Paulo. We intend to build a dialogue about the differences and convergences between the realities of two centuries, promoting reflection about the following problems: How the factors of the past (20th century) influenced current context in Sorocaba’s Childhood Education, considering formation, practices and motivation for and from teachers? We use as reference author such as Ecléa Bosi (1994; 2003), Jacques Le Goff (1984; 1990; 2003), Peter Burke (2005; 2010; 2011), Tizuko Morshida Kishimoto (1986; 1999), Moysés Kuhlmann Júnior (2000; 2011) and support in Oral History, using as method the narrative interview, with the purpose of register teacher’s memories who are also protagonists of Education’s History. Seven teachers were interviewed with ages about 32 and 80 years old. The register of their memories contributes to the comprehension of some of the Childhood’ Education’ problematics in town, indicating possible solutions